Implementation of Criminal Law Policy in Handling Narcotics Crimes at Asahan Police Station - Syamsuar, Noji; Kusbianto, Kusbianto; Zuliah, Azmiati (STAINI Press, 2026)
Narcotics crimes constitute serious offenses that threaten public security, public health, and social order. Their control requires the implementation of a comprehensive criminal law policy based on a clear normative framework. This article aims to analyze the implementation of criminal law policy in handling narcotics crimes at the Asahan Police Resort, the factors influencing its implementation, and the obstacles encountered. This study employs a normative juridical research method using statutory and conceptual approaches by examining legislation, legal doctrines, and relevant scholarly literature. The results indicate that criminal law policy on narcotics crimes has been normatively regulated under Law Number 35 of 2009 on Narcotics; however, its implementation still faces challenges, including limited supporting facilities, constraints in law enforcement capacity, and the complexity of narcotics-related crimes. Therefore, strengthening an integrated and effective criminal law policy is essential to enhance law enforcement performance.